2012
DOI: 10.4088/jcp.11m07614
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Clinical Manifestations and Outcomes Among Hospitalized Patients With Behavioral and Psychological Symptoms of Dementia

Abstract: The data demonstrated gender differences in BPSD and outcomes among hospitalized patients. The findings should be considered when deciding on the optimal management plan for patients with BPSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 0 publications
11
27
0
Order By: Relevance
“…In a previous study [12] on hospitalized patients with BPSD, we found that the profile of men at the time of admission was different to that of women: specifically, men were younger, more frequently had vascular dementia, were more frequently admitted from medical hospitals, had lower MMSE and N-ADL scores, were more frequently admitted because of combative behavior, and exhibited aggressiveness and diurnal rhythm disturbances on the BEHAVE-AD. These factors have been shown in the present study to be potentially associated with a longer period of hospitalization.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a previous study [12] on hospitalized patients with BPSD, we found that the profile of men at the time of admission was different to that of women: specifically, men were younger, more frequently had vascular dementia, were more frequently admitted from medical hospitals, had lower MMSE and N-ADL scores, were more frequently admitted because of combative behavior, and exhibited aggressiveness and diurnal rhythm disturbances on the BEHAVE-AD. These factors have been shown in the present study to be potentially associated with a longer period of hospitalization.…”
Section: Discussionmentioning
confidence: 96%
“…UFDs were defined as death during hospitalization or patient transfer to a medical hospital because of their deteriorating physical condition [12]. …”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of behavioral symptoms might explain the observed difference between men and women. Previous studies have reported that women experience behavioral symptoms, especially depressive symptoms, more frequently than men [14, 45, 46]. We compared the prevalence of behavioral symptoms in the US cohort and only depression and dysphoria were more frequently reported by women.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our data suggest that RIG-1 signaling activation results in increased expression of APP and Aβ, and that in addition Aβ contributes to the expression of RIG-1. It is important to consider that this study used samples from individuals in the MCI group that had a slightly greater number of females and a wider age range; thus, when interpreting these results one must take into account the effects of gender and age [40]. …”
Section: Discussionmentioning
confidence: 99%